Approaches for corneal endothelium regenerative medicine. (March 2022) - Català, Pere; Thuret, Gilles; Skottman, Heli; Mehta, Jodhbir S.; Parekh, Mohit; Ní Dhubhghaill, Sorcha; Collin, Rob W.J.; Nuijts, Rudy M.M.A.; Ferrari, Stefano; LaPointe, Vanessa L.S.; Dickman, Mor M.
Abstract: The state of the art therapy for treating corneal endothelial disease is transplantation. Advances in the reproducibility and accessibility of surgical techniques are increasing the number of corneal transplants, thereby causing a global deficit of donor corneas and leaving 12.7 million patients with addressable visual impairment. Approaches to regenerate the corneal endothelium offer a solution to the current tissue scarcity and a treatment to those in need. Methods for generating corneal endothelial cells into numbers that could address the current tissue shortage and the possible strategies used to deliver them have now become a therapeutic reality with clinical trials taking place in Japan, Singapore and Mexico. Nevertheless, there is still a long way before such therapies are approved by regulatory bodies and become clinical practice. Moreover, acellular corneal endothelial graft equivalents and certain drugs could provide a treatment option for specific disease conditions without the need of donor tissue or cells. Finally, with the emergence of gene modulation therapies to treat corneal endothelial disease, it would be possible to treat presymptomatic patients or those presenting early symptoms, drastically reducing the need for donor tissue. It is necessary to understand the most recent developments in this rapidly evolving field to know which conditions could be treated with which approach. This article provides an overview of the current and developing regenerative medicine therapies to treat corneal endothelial disease and provides the necessary guidance and understanding towards the treatment of corneal endothelial disease.